STRATEGI PENGEMBANGAN EKOWISATA KUNANG-KUNANG (Firefly) DI KAWASAN HUTAN MANGROVE DESA BOKOR KECAMATAN RANGSANG BARAT PROVINSI RIAU - Arief Rachman; Aras Mulyadi; Dessy Yoswaty (Fakultas Perikanan dan Kelautan, Universitas Riau, 2016)
Research on development strategy of fireflies (kunang-kunang) ecotourism is carried out in the mangrove forest Bokor village, district West Rangsang, Meranti Islands of Riau Province in October-November 2015. The purpose of this study is to see the public perception and composing development strategy of Firefly (Kunang-Kunang) ecotourism in mangrove forest Bokor village. The method used is a survey method and interview. Processing data using Respondents Perception Index (IPR) and SWOT analysis. Respondents Perception Index (IPR) are in the neutral category with score of 0.48 and the same perception Bokor village societies are in the category of being with a mean value of 2.25.Based on the SWOT analysis mangrove forest area Bokor village the potential for firefly ecotourism development with the position of matrix grand strategy in quadrant I.